PENGARUH MODEL PEMBELAJARAN LANGSUNG TERHADAP PENINGKATAN KOSA KATA WARNA ANAK TUNAGRAHITA RINGAN KELAS 4 DI SLB MUHAMMADIYAH LAMONGAN - Uswatun Hamidah (Universitas Trilogi, 2020)
The Influence of Direct Learning Models on Improving Vocational Vocabulary of Children Tunagrahita Light Class 4 In SLB Muhammadiyah Lamongan. The limitations of intelligence possessed by mild retarded children, indirectly inhibit the mastery of vocabulary, especially in the material to recognize color. The application of direct learning can improve the ability of mastering vocabulary to recognize colors (indicating and naming primary colors (red, yellow, blue) and secondary (orange, green, purple)) mildly retarded children in grade 4 at SLB Muhammadiyah Lamongan. The influence of direct learning models on increasing the color vocabulary of mild retarded children in grade 4 at SLB Muhammadiyah Lamongan. Thus, the use of direct learning models in learning Indonesian is already effective. This can be seen by a significant increase in student activity and student learning outcomes.